2016
DOI: 10.15761/cmid.1000113
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Elimination in Haiti: Challenges, Progress and Solutions

Abstract: Malaria continues to persist in Haiti, with 17,583 reported cases in 2015. The island of Hispaniola, the last locale of malaria in the Caribbean, recently adopted a bi-national agreement between the Dominican Republic and Haiti with the goal of eliminating malaria by 2020. In January 2015, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Numerous studies have established the importance of tailoring community-based elimination interventions to the local sociocultural context to increase their effectiveness and uptake [ 21 , 22 ]. However, very little is known about community perceptions in Haiti regarding malaria in general, and these community-based interventions in particular—an evidence gap that has recently been acknowledged in the literature [ 19 , 23 , 24 ]. The goal of this study was to develop a robust understanding of how to tailor, implement and promote malaria elimination strategies that could be considered by the Haitian Ministry of Health and its partners.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have established the importance of tailoring community-based elimination interventions to the local sociocultural context to increase their effectiveness and uptake [ 21 , 22 ]. However, very little is known about community perceptions in Haiti regarding malaria in general, and these community-based interventions in particular—an evidence gap that has recently been acknowledged in the literature [ 19 , 23 , 24 ]. The goal of this study was to develop a robust understanding of how to tailor, implement and promote malaria elimination strategies that could be considered by the Haitian Ministry of Health and its partners.…”
Section: Introductionmentioning
confidence: 99%
“…Further study revealed the Nepalese origins of this strain (35). The lab also plays follows the ongoing progress in the elimination of malaria in Haiti (36).…”
Section: The Role Of the Laboratory In The Health Systemmentioning
confidence: 83%
“…Altogether, this evidence suggests that targeting activities to the geographically clustered cases is warranted in Artibonite, where 60% of all hsRDT-positive cases were identified at two adjacent venues [35,36]. By contrast, transmission is still relatively high in Grand'Anse, warranting broader and more intensive control interventions with any targeting focused on the coast [2,3].…”
Section: Discussionmentioning
confidence: 98%
“…Haiti and the Dominican Republic are committed to eliminating malaria [1][2][3]. The island they share (Hispaniola) remains the only one in the Caribbean with endemic malaria transmission, with the majority of cases being reported in Haiti [2,4].…”
Section: Introductionmentioning
confidence: 99%